Temporal Changes in Characteristics, Treatment and Outcomes of Heart Failure Patients Undergoing Percutaneous Coronary Intervention Findings from Melbourne Interventional Group Registry - Chin, K.; Tacey, M.; Reid, Christopher; Tonkin, A.; Hopper, I.; Brennan, A.; Andrianopoulos, N.; Duffy, S.; Clark, D.; Ajani, A.; Liew, D. (Elsevier, 2018)
Background: Limited data exist on whether outcomes of patients with heart failure (HF) undergoing percutaneous coronary intervention (PCI) have improved over time. The purpose of this study was to assess temporal trends in patient characteristics, treatment and outcomes of patients with HF undergoing PCI. Methods: Using data from the Melbourne Interventional Group (MIG), we evaluated temporal trends of procedure volume, major adverse cardiac events (MACE; a composite of all-cause mortality, myocardial infarction and target vessel revascularisation) and rates of cardiovascular readmission, all-cause death and cardiovascular death in consecutive patients with HF undergoing PCI. Change over time was assessed by Box-Jenkins autoregressive integrated moving average (ARIMA) models. Results: Data from 1604 patients were analysed. In our cohort, there were no significant changes in the number of procedures performed annually and patient characteristics between January 2005 and December 2014. Optimal use of HF therapy has improved over the study period. Planned clopidogrel therapy of more than 12 months increased in tandem with increasing use of drug-eluting stents (DES). Procedural success was high (=90%). However, the rates of MACE, cardiovascular readmission, all-cause death and cardiovascular death remained unchanged throughout the study period. Conclusions: Clinical outcomes in HF patients undergoing PCI have remained unchanged despite improvement in medical technology and contemporary therapeutic measures.